Pemasaran Wisata Berbasis Website di Nagari Wisata Harau Kabupaten Lima Puluh Kota - Putra, Trisna; Pasaribu, Pasaribu; Wulansari, Nidia (Abdi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
The challenge of tourism destination in industrial revolution 4.0 is the existence of its information system. Website becomes one of the potential media to promote positive image of a tourism destination. Nagari Harau is one of potential tourist destinations at Lima Puluh Kota Regency, West Sumatera. However it’s an existence as well as potencies was not sufficiently published on the internet. The main obstacle of this problem is the capability of the management, in this case called a pokdarwis, in promoting it at the internet through its official website. Thus in order to overcome the problem, a public service program was design to empower the member of pokdarwis in Nagari Harau. The method used in public service program is action learning. The result of the program after having a post test toward the participants is 95% for cognitive aspect, 95% for affective aspect and 85% for conative aspect. The result show that the participants enthusiasm to the program and their increasing capability as well as capacity in promoting destination through website